Maximizing Guest Satisfaction and Financial Benefits: An Integrated Approach in Wimarion Hotel Management - Intiar, Septa; Rahayu, Enik; Prabowo, Bayu Ade; Yuliamir, Henry (Indonesian Journal of Economics and Management, 2024)
This study delves into an integrative management approach within the context of Wimarion Hotel, with a dual focus on augmenting guest satisfaction and enhancing financial viability. Through the incorporation of pivotal factors encompassing front office services, pricing dynamics, customer communication strategies, interior design aesthetics, and overarching business strategies, the research endeavors to pinpoint variables that can be optimized to synergistically boost employee productivity and fiscal gains. Employing a quantitative cross-sectional methodology, data was gathered from a sample of 100 randomly chosen hotel patrons via questionnaire dissemination. Analysis underscores a statistically significant positive correlation between guest satisfaction, financial profitability, and the realization of an integrated management framework. These findings underscore the imperative of adopting comprehensive strategies in hotel administration, underscoring the intrinsic linkages between guest contentment and fiscal prosperity in achieving overarching management cohesion.